PERILAKU PEREMPUAN PEDESAAN DALAM MENCARI DAN MENEMUKAN INFORMASI MENGENAI KESEHATAN REPRODUKSI - Rosfiantika, Evi (Universitas Pendidikan Indonesia, 2012)
The high mortality of mothers and babies, can be prevented one of them with the convenience of women access information about reproductive health. women who have sufficient knowledge can take appropriate action to maintain and maintain their reproductive health, The more problems that exist about reproductive health, the provision of information is very important, with the correct and accurate information women will have the understanding and awareness to be healthy in the function and process of reproduction. This article is based on research results in leuwigoong Garut about the behavior of rural women in accessing information about reproductive health. The aim is to find out how rural women seek and find information on reproductive health. The method used in this research is descriptive method with qualitative approach. Data collection tools such as interviews, observation, and literature study. The results showed that rural women's behavior in accessing information on reproductive health, based on the need to improve the quality of healthy life during the process of reproduction. Information obtained from the nearest source of information, namely parents, midwives, hereditary advice and the people closest. The mass media does not get an important position for them to access information. The information found is used for oneself and spread verbally to the people closest to the environment.